Yakut-Even Folklore Correlations in Epic Genres of the Evens of Yakutia - Burykin, Alexey Alexeyevich (Journal of History Culture and Art Research, 2018)
The topic of article focuses on the examples of epic and fantastic genres interaction represented in the Yakut and Even folklore traditions. The author takes examples from the texts and describes some fragments of Yakut and Even epic texts in which there is an ornitomorphic feature connected with the name Yoksyokyu, and in the Evens texts – with the name Yugseki or Yevseki. This feature is present in various examples of epic texts of the Yakut traditional epic olonkho and in some folklore texts of the Dolgans; it can be seen in the epic legends of the southeast Evens, living in the Khabarovsky Krai, who have come there from the east of Yakutia and are presently living in the neighboring regions with the Yakut people. Apart from epic texts, the image of a bird of Yoksyokyu occurs in examples of Dolgan and Yakut fairy tales. In our research, the descriptive method was used providing a large scope of primary textual data analysis; as well as the categorizing method allowing to show specific features of each text and its details; the comparative method aimed at defining similarities and differences in the context of both – the Yakut and Tungus folklore traditions and texts, representing different genres – the epic olonkho and fairy tales. A text material was selected using the method of computer analysis of large scope of texts, allowing taking texts containing proper names, age and social signs of characters, living beings and subjects as well as these subjects' names. Occurrence of such a character as a predatory fighting bird Yugseki similar to an eagle – Yevseki in the Even legends – is an unequivocal cultural borrowing from the Yakut folklore tradition: the group of Evens where these legends have been written down, is native to the Ust-Maya ulus (administrative division) of Yakutia and their dialect is close to the Even dialects of eastern Yakutia. In all Yoksyokyu referred to in the texts – the ornitomorphic character with a number of heads ranging from 1 to 8, capable of turning into a well-built human being and of participating in epic hero duels. It is a typical example of a cultural borrowing: in folklore, separate motifs and the characters connected with such motifs are usually borrowed. The image of Yoksyokyu – the birdlike human represents such type of a hero as the mediatory force connecting the different worlds (in this case the world of people and birds as a category of characters and Middle (terrestrial) and Top (Upper) worlds as spheres of action and narrations. The given example of character borrowing from the Yakut folklore tradition by the Even epic tradition is a rather bright one and the attention of researchers is drawn to it, but it appears by far not the only thing in weight of examples displaying influence that the Yakut folklore had on that of the Evens.